To The Question About the Concept of a Notary in the Russian Federation - Shevchenko, Sergey N. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
In this article the Author analyzes various approaches to the definition of the notaries in the legal science of the Russian Federation: definition of the notary as organ systems and how collectively notarial acts. Proves the fallacy of the position of the individual authors of administratively identifying the notaries to the system of law enforcement and supports the view of experts of civil law on the attribution of notaries to authorities undisputed civil jurisdiction. Based on the above, the Author proposes the definition of a notary.